Needs Analysis of Ngidang-Based Digital Storybooks for Moral Education in Children Aged 5–6 Years - Elfina Rahmawati; Sri Sumarni; Suratmi (Journal of Islamic Education Students (JIES), 2026)
This study aims to analyze teachers' needs for digital storybooks based on the local wisdom of the "ngidang" tradition of Palembang as a medium for learning moral values for children aged 5–6 years. The study used a quantitative descriptive approach with 29 kindergarten teachers in Palembang as subjects. Data were collected through a Google Form-based questionnaire and written interviews. The questionnaire instrument covered five aspects: limitations of learning media, the need for innovative media, children's attention problems with conventional media, perceptions of digital storybooks, and teachers' readiness and support in using digital media. Data analysis was carried out by calculating percentage scores. The results showed that all aspects obtained percentages above 70%, indicating a high need for teachers for digital storybooks as a medium for instilling moral values. Teachers stated that available learning media were still limited and children easily bored with conventional methods. In addition, teachers had a positive perception of digital storybooks, which were considered able to improve attention, understanding, and the quality of learning. Interview findings also confirmed that digital storybooks based on local wisdom were considered relevant, interesting, and effective in instilling moral values such as togetherness, empathy, and responsibility. This shows that the development of digital story books based on the Palembang ngidang tradition is considered necessary and contains high urgency as an innovative media for learning moral values for children aged 5-6 years.